Comparing Conservative Treatment of Distal Ulna Fractures with Operative treatment - Waseem Ahmed, Mushtaque Ahmed Shaikh, Ahmed Raza Laghari, Babar Jan, Muhammad Younis, Sartaj Lakhani, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the outcome of conservative treatment of distal ulna fractures with operative treatment Study design: A randomized control trial Place and duration: This study was conducted at Muhammad Medical College and Hospital Mirpurkhas from September 2021 to September 2022 Methodology:Patients with different types of ulnar fractures (base fractures, head fractures, and subchondral fractures) were divided into two groups based on a systematic approach that established the course of treatment for forearm fractures. The fractures of the distal radius in Group A were treated with plating osteosynthesis, while the fractures of the distal ulna were taken care of with a surgical procedure involving the implantation of an LCP Distal Ulna Plate (De PuySynthes, USA) Results: A total of 120 patients were enrolled in the study, 8 of whom had to be excluded due to the development of carpal ligament damage symptoms. The 112 patients who remained were divided into three groups: 36 in group A, 42 in group B, and 34 in group C. The results of distal forearm fractures were initially treated with closed repositioning in local anesthesia and plaster fixation in 89 cases. In 10 cases, external fixation was primarily applied due to soft tissue conditions. The definitive surgical procedure was performed on average 10 days (3-19) from the injury. In group A, osteosynthesis of both bones was performed during one operation in 30 patients. In 7 cases, it was necessary to perform a two-phase procedure due to the state of the soft tissues. Conclusion: Based on the study's results, osteosynthesis is the more successful treatment for sub-capital fractures, as it results in better early outcomes than a conservative approach. However, due to the low number of patients with this type of fracture, it is impossible to make definitive treatment recommendations Keywords: distal ulnar fracture, osteosynthesis, conservative treatment